2019
DOI: 10.1038/s41598-019-51841-2
|View full text |Cite|
|
Sign up to set email alerts
|

Neural control of fasting-induced torpor in mice

Abstract: Torpor is a peculiar mammalian behaviour, characterized by the active reduction of metabolic rate, followed by a drop in body temperature. To enter torpor, the activation of all thermogenic organs that could potentially defend body temperature must be prevented. Most of these organs, such as the brown adipose tissue, are controlled by the key thermoregulatory region of the Raphe Pallidus (RPa). Currently, it is not known which brain areas mediate the entrance into torpor. To identify these areas, the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…Pioneering studies have identified hypothalamic nuclei and circuits that are critically involved in regulation of body temperature and metabolism 9 , 12 , 98 . Our tracing studies reveal projections from ERα + neurons to several of these hypothalamic nuclei, including the DMH, VMH, and ARC.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering studies have identified hypothalamic nuclei and circuits that are critically involved in regulation of body temperature and metabolism 9 , 12 , 98 . Our tracing studies reveal projections from ERα + neurons to several of these hypothalamic nuclei, including the DMH, VMH, and ARC.…”
Section: Discussionmentioning
confidence: 99%
“…To examine neural mechanisms underlying stress-induced sleep-like inactivity, we examined c-Fos expression, a histological marker for neuronal activity, in brain regions related to sleep and wake regulations 13 , 31 after either social defeat stress or cage transfer. The stress did not affect c-Fos expression in sleep-promoting brain regions, VLPO and MnPO (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although whether DMH neurons can regulate total sleep is not reported, the activation of VLPAG neurons reduced wake periods along with increased non-REM sleep in a previous study 15 . Interestingly, these brain regions are activated by torpor-inducing stimuli 31 , such as fasting and cold exposure, and the DMH is crucial for optogenetically induced hibernation-like state 33 . Consistent with the activation of these brain regions, we found that social defeat stress decreases body temperature in a manner correlated to the proportion of active periods.…”
Section: Discussionmentioning
confidence: 99%
“…The use of infrared thermography has the potential to provide a non-invasive method to measure T core but its own methodological limitations have to be taken into account 5,6 . Previous applications of non-contact T skin measurements in biomedical research have been limited by the requirement that animals needed to be handled by the experimenter [7][8][9][10][11][12][13][14][15] , measurements were taken at a limited number of timepoints 7,8,[10][11][12][13][14][15][16][17] , and/or measurements resulted in large datafiles requiring complex data analysis 10,12,13,[16][17][18] . The present study developed, optimised and validated an algorithm that enables estimation of relative changes in T core based on the continuous and non-invasive automated measurement of T skin of mice housed at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ methods typically require animal handling, are not continuous, and do not measure T core [7][8][9][10][11][12][13][14][15][16][17][18] . The non-invasive nature of thermography measurements does however provide the potential to assess body temperature in undisturbed freely-moving laboratory mice, removing the confounding factor of handling stress and representing an obvious refinement in terms of animal welfare.…”
Section: Scientific Reportsmentioning
confidence: 99%